Persian Quotations in the Haqq Al-Yaqin fi Aqidat Al-Muhaqqiqin fi Dhikr Asrar Sufi Al-Muhqqiqin of Shaykh Shams Al-Din Al-Sumatra'i (d.1639 CE) - Mohamad Nasir, Mohamad Nasrin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Persian Quotations in the Haqq Al-Yaqin fi Aqidat Al-Muhaqqiqin fi Dhikr Asrar Sufi Al-Muhqqiqin of Shaykh Shams Al-Din Al-Sumatra'i (d.1639 CE)